1986
DOI: 10.1021/bi00368a009
|View full text |Cite
|
Sign up to set email alerts
|

Thermostability of double-stranded deoxyribonucleic acids: the effects of covalent additions of a psoralen

Abstract: We have carried out a thermodynamic study on the effects of covalent additions of the psoralen derivative H M T , 4'-(hydroxymethyl)-4,5',8-trimethylpsoralen, on the stability of double-stranded deoxyoligonucleotides. This was done with two systems. The first was a double-stranded D N A formed by two non-self-complementary oligonucleotides, 5'-GAAGCTACGAGC-3' and S-GCTCGTAGCTTC-3', where we site specifically placed an H M T molecule on the thymidine residue in oligonucleotide 5'-GAAGCT-ACGAGC-3' as either a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
25
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 26 publications
8
25
0
Order By: Relevance
“…These robust catalytic efficiencies are observed on DNAs containing either abasic site-linked peptides (8,67) or γ-OH-PdG-linked peptides (6) even though these lesions stabilize, rather than destabilize duplex DNA. These data are similar to prior studies that investigated the structure−activity relationship of psoralen monoadducted DNAs and the UvrABC complex (6870). Although the psoralen monoadduct stabilized the DNA duplex, the UvrABC system recognized and incised it with a very high efficiency, while in contrast, it was a very poor substrate for the human NER complex (70).…”
Section: Discussionsupporting
confidence: 88%
“…These robust catalytic efficiencies are observed on DNAs containing either abasic site-linked peptides (8,67) or γ-OH-PdG-linked peptides (6) even though these lesions stabilize, rather than destabilize duplex DNA. These data are similar to prior studies that investigated the structure−activity relationship of psoralen monoadducted DNAs and the UvrABC complex (6870). Although the psoralen monoadduct stabilized the DNA duplex, the UvrABC system recognized and incised it with a very high efficiency, while in contrast, it was a very poor substrate for the human NER complex (70).…”
Section: Discussionsupporting
confidence: 88%
“…In comparison, BPDE-N 2 -guanine adducts exert more moderate effects on double-helical stability (16,17,24). Psoralen monoadducts, on the other hand, slightly increase helical stability (19,20,28), whereas anthramycin and CC-1065 adducts produce substantial increments in helical stability (21,22). Thus, an early subset of NER factors appears to be endowed with the capacity to sense thermodynamic parameters of double-stranded DNA and preferentially interact with those sites that exhibit unfavorable changes in free energy.…”
Section: Discussionmentioning
confidence: 99%
“…Melting temperature studies have shown that these bulky base adducts alter the thermodynamic characteristics of DNA in different ways. AAF adducts (14,15), BPDE adducts (16,17) and UV radiation products (18) destabilize the DNA double helix relative to nonmodified DNA, whereas 8-MOP (19,20), anthramycin (21), and CC-1065 adducts (22) stabilize the DNA duplex. In the predominant adduct formed by N-acetoxy-2-acetylaminofluorene (AAF-C 8 -guanine), the modified base is rotated out of the helix axis, and the duplex is locally denatured (14,23).…”
Section: Nucleotide Excision Repair (Ner)mentioning
confidence: 99%
See 1 more Smart Citation
“…Agents which give rise to interstrand linkage are potential antitumor drugs (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Cross-linking strongly influences biological and physical properties of DNA molecule (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and alters DNA structure and melting behavior (25,(37)(38)(39)(40)(41)(42). At the same time DNA conformation influences cross-link formation (36).…”
Section: Introductionmentioning
confidence: 99%